2019
DOI: 10.3390/su11154049
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Knowledge Sharing and Innovation on Sustainable Performance in Islamic Banks: A Mediation Analysis through a SEM Approach

Abstract: This research is among the very few studies seeking a focalized examination on the relationship between knowledge sharing within a firm and organizational innovation. This specific study establishes that the knowledge sharing and innovation processes in Islamic banks are integral parts of the survival and progress of business organizations. Knowledge sharing and creativity are essential elements in the development of innovative strategies, but few studies have sought to investigate this relationship. This stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 92 publications
(65 citation statements)
references
References 118 publications
1
61
1
2
Order By: Relevance
“…The idea that innovation is essential to an organization to remain competitive, sustained, and successful was widely recognized [62][63][64][65]. Organizational innovation involves the formulation of innovative products and services, methods, and new ideas.…”
Section: The Relationship Among Knowledge Management Organizationalmentioning
confidence: 99%
“…The idea that innovation is essential to an organization to remain competitive, sustained, and successful was widely recognized [62][63][64][65]. Organizational innovation involves the formulation of innovative products and services, methods, and new ideas.…”
Section: The Relationship Among Knowledge Management Organizationalmentioning
confidence: 99%
“…Some studies have highlighted that this relationship might be mediated by some other factors that indirectly influence it and suggested that the mediators should be examined to understand the influence of CEO duality on firm performance [13,14]. We addressed this research gap by using two variables (capital structure and market competition) as parallel mediators to explain the relationship between CEO duality and firm performance [101][102][103][104][105].…”
Section: Conclusion and Future Directionmentioning
confidence: 99%
“…Prior studies [59][60][61][62] have indicated that through well-designed training, creativity can be elevated and further enhances the skill and efficacy of individual employee, which will have a flow on effect to the collective innovation process. This can significantly contribute to the overall effectiveness and growth of sustainable operations in a corporation [4][5][6]. This study will focus on investigating the impact of communication formats (specifically CMC and FtF) in creativity training on potential creativity, which seek to address the two proposed research questions identified earlier.…”
Section: Creativitymentioning
confidence: 99%